2018
DOI: 10.1016/s0140-6736(18)32558-3
|View full text |Cite
|
Sign up to set email alerts
|

Health impacts of parental migration on left-behind children and adolescents: a systematic review and meta-analysis

Abstract: SummaryBackgroundGlobally, a growing number of children and adolescents are left behind when parents migrate. We investigated the effect of parental migration on the health of left behind-children and adolescents in low-income and middle-income countries (LMICs).MethodsFor this systematic review and meta-analysis we searched MEDLINE, Embase, CINAHL, the Cochrane Library, Web of Science, PsychINFO, Global Index Medicus, Scopus, and Popline from inception to April 27, 2017, without language restrictions, for obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
345
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 405 publications
(375 citation statements)
references
References 72 publications
26
345
0
4
Order By: Relevance
“…The present study broadly supports the previous findings that parental migration was not significantly detrimental to child nutrition [13,16,22,36] and even confirm the benefits of paternal migration on early childhood nutrition of rural children [13,37,38], despite contrary results found in other studies [5,18,39]. A decreasing difference in early childhood nutrition between children with various parental migration statuses was shown in recent years, and in the survey in 2016, no significant differences in risks of stunting, underweight, and wasting were detected between them.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study broadly supports the previous findings that parental migration was not significantly detrimental to child nutrition [13,16,22,36] and even confirm the benefits of paternal migration on early childhood nutrition of rural children [13,37,38], despite contrary results found in other studies [5,18,39]. A decreasing difference in early childhood nutrition between children with various parental migration statuses was shown in recent years, and in the survey in 2016, no significant differences in risks of stunting, underweight, and wasting were detected between them.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, some studies identified a higher risk of anemia among left-behind than non-left-behind children [16,17], but other work found no such difference [14]. A recent systematic review and metaanalysis of these studies done from 1994 to September 2018, 82% of which were conducted in China, found that, compared with non-left-behind children, left-behind children had a significantly increased risk of wasting and stunting, but a similar risk of underweight and anemia [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with children of non-migrants, left-behind children and adolescents had a 52% increased risk of depression, 70% increased risk of suicidal ideation and 85% increased risk of anxiety. 6 A global school-based student health survey among Nepali adolescents aged 13-17 years showed that lower perceived parental engagement was significantly associated with higher odds for suicide attempt and anxiety in both boys and girls. 7 These findings suggest a need for focused mental health-related interventions aimed at left-behind adolescents.…”
Section: Evidence On the Mental Health Of Leftbehind Adolescentsmentioning
confidence: 99%
“…The most imminent and relevant global issue that is closely linked to world health is probably climate change. 2 Climate change has direct negative local effects (eg, droughts, flooding, and famine) and supraregional repercussions (eg, migration). Although the biggest por tion of medical resources is allocated to the socalled developed world, most of the affected people live in low income and middleincome regions.…”
Section: Inequality World Health and Global Governancementioning
confidence: 99%